Marriage Norm Reflected At Okky Madasari's The Outcast Novel (2014); A Psychoanalytic Approach - Allansari, Catrine Diah, Dr. Phil. Dewi Chandraningrum, S. Pd. M. Ed, Titis Setyabudi, S.Si (2015)
The major problem in this study is how the major character proves her faith and love in The Outcast (2014) novel by Okky Madasari. This study focused on the one of the major characters namely Maryam, using the means of psychoanalytic analysis. The object of this study is Okky Madasari The Outcast novel published in 2014 by Gramedia pustaka. The type of this study is descriptive qualitative. The primary data source is the novel The Outcast itself and the secondary data source is books or any information related to the practice of faith, marriage norm and love that support the psychoanalytic approach by Sigmund Freud. The technique of analyzing data in this research paper is descriptive.The researcher concludes that love and faith is the individual emotions, it drives from system of personality. When id wants to satisfy soon, superego must consider it with morality. It can be said that superego give a pressure on id and it causes the conflicts in the personality. Okky Madasari gives the important points when the major character, Maryam, gets the conflict between her id and superego to prove her love.The outcome of the study shows that the problem faced by the major character Maryam causes the conflict of her mental condition. It comes because her struggle to proves her faith and love for her life. Finally, her effort makes her suffer until the end.